2023
DOI: 10.3390/genes14071307
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Novel SPHINX/BMMF-like DNA Sequences Isolated from Non-Bovine Foods

Abstract: Sixteen novel circular rep-encoding DNA sequences with high sequence homologies to previously described SPHINX and BMMF sequences were isolated for the first time from non-bovine foods (pork, wild boar, chicken meat, Alaska pollock, pangasius, black tiger shrimp, apple, carrot, and sprouts from alfalfa, radish, and broccoli). The phylogenetic analysis of the full-length circular genomes grouped these together with previously described representatives of SPHINX/BMMF group 1 and 2 sequences (eight in each group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Specifically, the relation of SPHINX/BMMF group 2 to rolling circle replicating plasmids fits with the detected conserved dso/sso regions mentioned above, because these dso/sso regions were also found in rolling circle-type plasmids [19]. The question which then remains is if SPHINX/BMMFs are plasmids, in which host are these contained?…”
Section: Is Sphinx/bmmf Dna Viral or Plasmid Dna?supporting
confidence: 78%
See 2 more Smart Citations
“…Specifically, the relation of SPHINX/BMMF group 2 to rolling circle replicating plasmids fits with the detected conserved dso/sso regions mentioned above, because these dso/sso regions were also found in rolling circle-type plasmids [19]. The question which then remains is if SPHINX/BMMFs are plasmids, in which host are these contained?…”
Section: Is Sphinx/bmmf Dna Viral or Plasmid Dna?supporting
confidence: 78%
“…Clearly, these are unsolved questions which should be addressed in further studies. [10,13,14,18,19,30]. Schematic image of the regulatory region (framed), which potentially includes oriT (green) [19], AT-rich region (potential origin of replication, grey) [19,31] and iteron-like tandem repeats (ITRs, orange) [19].…”
Section: Is Sphinx/bmmf Dna Viral or Plasmid Dna?mentioning
confidence: 99%
See 1 more Smart Citation
“…All previous studies testing for the presence of BMMF DNA have used a combination of rolling circle amplification (RCA) and subsequent BMMF DNA PCR. Of interest, two recent studies have reported the finding of BMMF DNA in an amazingly broad spectrum of food sources, possibly indicating that BMMFs are not solely of bovine origin and are widespread [8,9]. Although these findings await confirmation by others, the sheer finding of exogenous DNA in human tissues and body fluids, which is capable of replicating in HEK cells, is of significant concern.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that non-pathogenic persistent infections in animals and their products might be pathogenic if transmitted to humans [5]. BMMF DNAs have also been identified in the milk from water buffaloes, sheep, and goats, among others [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%